Mental health risk in human services work across Europe: the predictive role of employment in various sectors - Ágnes Győri; Éva Perpék; Szilvia Ádám (Frontiers in Public Health)
BackgroundHuman services occupations are highly exposed to mental health risks, thus psychosocial risk management is critical to assure healthy and safe working conditions, promote mental health and commitment, and prevent fluctuation of employees. However, still little is known about prominent psychosocial risk factors in various human services work.ObjectivesTo identify prominent psychosocial risk factors of mental health in human services occupations and to explore their individual and organizational correlates in 19 European countries.MethodsCross-sectional survey using data from the European Union's Labor Force Survey among 379,759 active employees in 19 European countries. First, a descriptive analysis was carried out to establish the prevalence of mental health risk factors. Then sociodemographic correlates of occupational mental health risk factors were assessed by means of Pearson's chi-squared test. Finally, correlations were explored between perceived psychosocial risk factors and human vs. non-human services occupations, as well as contextual variables by applying multilevel logistic and multinomial regression analyses.ResultsThe prevalence of mental health risk was 45.1%. Work overload (19.9%), dealing with difficult clients (10.2%), and job insecurity (5.8%) were the most prevalent mental health risk factors among European employees. We identified significant differences in the prevalence of mental health risks and specific mental health risk factors among employees according to sex, age, and educational attainment. The prevalence of mental health risks was significantly higher among women (47.0%, man: 43.3%), workers aged 35–50 years (47.5%, >50: 44.4%, <35: 42.3%), and those with the higher level of education (51.9%, secondary with diploma: 42.6%, elementary: 36.2%). Employees working in healthcare in Northern Europe were most likely to be exposed to mental health risks (AME = 0.717). Working in healthcare in Northern Europe was the strongest predictor of reporting work overload (AME = 0.381). Working in social care in Central and Eastern Europe was the strongest predictor of reporting dealing with difficult clients (AME = 0.303) as the most prevalent mental health risk factor.ConclusionUnderstanding the impact of employment in specific human services occupations on mental health and its specific occupational stressors are vital to improve mental health and safety at work and maintain high quality services.